2013
DOI: 10.1364/ome.3.000624
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser deposition of high-quality μm-thick YIG films on YAG

Abstract: We report the epitaxial growth of high-quality μm-thick yttrium iron garnet (YIG) films on yttrium aluminium garnet (YAG) substrates by pulsed laser deposition (PLD). The effects of substrate temperature and oxygen pressure on composition, crystallinity, optical transmission and ferromagnetic resonance (FMR) linewidth have been investigated. An FMR linewidth as low as 1.75 mT at 6 GHz was achieved by depositing YIG on YAG substrates with (100) orientation at a substrate temperature of ~1600 K and with oxygen p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 25 publications
4
19
1
Order By: Relevance
“…Single-beam PLD from a stoichiometric target usually leads to films that are iron (Fe) deficient, as previously reported in the literature [2] and confirmed in our experiments [5].…”
Section: Introductionsupporting
confidence: 91%
See 2 more Smart Citations
“…Single-beam PLD from a stoichiometric target usually leads to films that are iron (Fe) deficient, as previously reported in the literature [2] and confirmed in our experiments [5].…”
Section: Introductionsupporting
confidence: 91%
“…in magnetostatic wave band pass filters [2].YIG films have been grown by liquid phase epitaxy [3], sputtering [4] or pulsed laser deposition (PLD) [2,5]. Single-beam PLD from a stoichiometric target usually leads to films that are iron (Fe) deficient, as previously reported in the literature [2] and confirmed in our experiments [5].…”
supporting
confidence: 80%
See 1 more Smart Citation
“…The dielectric spacers are made of alternately placed layers of TiO 2 and SiO 2 with thicknesses of d 1 and d 2 , respectively, which will take values from 100 nm up to few hundreds of nm. Thus, such structure can be fabricated with available technologies 41,[68][69][70] and plays simultaneously the role of MC ( Fig. 1(a)) and PC ( Fig.…”
Section: Structurementioning
confidence: 99%
“…It was reported that Bi dopant decreased the saturation magnetization of Y 3 Fe 5 O 12 nanoparticles [14]. Additionally, considerable research studies, focused on the magnetic thin films, have been reported [15][16][17]. H. L. Wang et al [15] investigated the straintunable magnetocrystalline anisotropy in YIG thin films.…”
Section: Introductionmentioning
confidence: 99%